Evaluating buffer methods for determining lime requirement on acidified agricultural soils of the Palouse. Issue 5 (19th October 2020) - McFarland, Carol; Shiwakoti, Santosh; Carpenter‐Boggs, Lynne; Schroeder, Kurt; Brown, Tabitha; Huggins, David R.
Abstract: Acidification of agricultural soils under intense management in the Palouse region of eastern Washington and northern Idaho is of increasing concern. Buffer methods can provide lime requirement estimates (LREs); however, locally calibrated methods are lacking. Our objective was to evaluate buffer methods and to determine which can produce optimal LREs for Palouse agricultural soils. Samples from 10 regionally dominant agricultural soils (initial pH ≤5.3) were assessed for pH changes after incubation with nine levels of calcium carbonate (CaCO3 ) for 90 d under laboratory conditions. Achieving a target pH of 6 in the top 15 cm of the soil profile required 3.36–8.36 Mg ha −1 of CaCO3 . Laboratory incubation results were compared with LREs calculated from 10 established calibrations using data from seven buffer methods: Shoemaker–McLean–Pratt (SMP), Adams and Evans (AE), Woodruff 6, Woodruff 7, Western Region Woodruff 7, Sikora, and Modified Mehlich (MM). The SMP ( R 2  = .47) and AE ( R 2  = .56) calibrations demonstrated the lowest correlation with observed incubation lime requirement (LR) and are not recommended for use on Palouse soils. The MM ( R 2  = .90), Woodruff 6 ( R 2  = .78), and Woodruff 7 ( R 2  = .75) buffer calibrations produced the strongest correlation between LREs and the LRs determined by laboratory incubation. Combining organic matter (OM) with KCl‐extractable aluminum (KCl‐Al) or soil pH was also predictive of LR ( R 2  = .72) in a stepwise multivariate analysis. The recommendation from this study is to assess LR on Palouse soils using the MM buffer or to use soil analytical results and compute LR from OM and KCl‐Al or pH.